2014
DOI: 10.2134/agronj14.0234
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Lowering Soybean Planting Density without Compromising Nitrogen Fixation and Yield

Abstract: Adjusting soybean [Glycine max (L.) Merrill] density can be critical to reduce inter-plant competition for water, nutrients, and sunlight, and to increase intercepted radiation, photosynthesis, and biomass production. The objective of this study was to evaluate the effects of soybean-population density on soybean nodulation, plant nutrient status, yield, and grain quality. Three field experiments were performed in southern Brazil with soybean cultivar BRS 284, of indeterminate growth type and maturity group 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The higher number of side branches and, consequently, more pods per plant, with precision seeding compared to drill seeding did not lead to an increase in protein or oil content in soybean. However, an increase in crop density tends to lead to higher protein content [51,52] and since the two, i.e., protein and oil content, correlate negatively [53], oil content also increases with decreasing crop density by trend [54]. Our results showed that neither drill nor precision seeding reduced or increased protein content and oil content.…”
Section: Discussionmentioning
confidence: 53%
“…The higher number of side branches and, consequently, more pods per plant, with precision seeding compared to drill seeding did not lead to an increase in protein or oil content in soybean. However, an increase in crop density tends to lead to higher protein content [51,52] and since the two, i.e., protein and oil content, correlate negatively [53], oil content also increases with decreasing crop density by trend [54]. Our results showed that neither drill nor precision seeding reduced or increased protein content and oil content.…”
Section: Discussionmentioning
confidence: 53%
“…It is known that ∼40% of the dry soybean is composed of protein, resulting in a high demand for N, and that majority of this is supplied by BNF (Alves et al, 2003;Hungria et al, 2006;Luca et al, 2014). In this study, a low Ni rate (45 mg kg −1 ) stimulated BNF and the affect was most pronounced in the grains, in which it can be noticed that more of 90% of total N accumulated were derived from BNF ( Table 3).…”
Section: Discussionmentioning
confidence: 54%
“…In the maize-soybean intercropping system, the light was the most most-frequently limited factor under the condition of adequate water and the nutrient for crop growth and development [54][55][56][57]. In this study, there was a significant positive correlation between the net photosynthetic rate the available light for soybean plants.…”
Section: Light Environment and Photosynthesis Characteristicsmentioning
confidence: 53%